Predicted interaction of human Ribosomal Protein S15 with Fragile X Mental Retardation Protein - Ui-Hang, Edmund Sim; Xiang-Ru, Ma; Li-Li, Stella Chan; Choon-Weng, Lee; Kumaran, Narayanan (LLP, 2016)
In addition to the central role of ribosome biogenesis, the human ribosomal protein S15 (RPS15) has extra-ribosomal roles that include its association with a congenital disease and a few types of cancer. However, current knowledge of its functions in the context of extra-ribosomal activities remains fragmented. An approach to gain insights into the interaction between RPS15 and possible protein partners is via Bioinformatics strategies. Based on the sequence-to-structure-to-function paradigm, structural data of a protein can be computationally analysed to derive logical interacting partners. This method can include three-dimensional model construction, structural neighbour prediction, and molecular docking analysis. By using this approach, we have constructed RPS15 3D-structural models that have allowed the prediction of 23 structural neighbours. Of these, two that are from human origin were further analysed and only one have logical prospect of binary protein-protein interactions. Further analysis of this structural neighbour revealed 7 candidate docking partners. From these, our molecular docking analysis demonstrated two most logical dock models of interactions between RPS15 with two different domains of the Fragile X Mental Retardation Protein 1 (FMRP1) protein. Hence, we have provided in silico evidence of de novo protein-protein interaction between RPS15 and the Fragile X Mental Retardation Protein 1 (FMRP1).